2015
DOI: 10.1177/1368430214558310
|View full text |Cite
|
Sign up to set email alerts
|

International support for the Arab uprisings: Understanding sympathetic collective action using theories of social dominance and social identity

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 52 publications
6
72
1
Order By: Relevance
“…Several empirical studies that are in line with our findings explain that when performing collective action, the emotion felt by an individual is the group's emotion as a response to the situation experienced by their group, especially anger (Shepherd et al, 2013;Shi et al, 2014; Stewart et al, 2015;van Zomeren et al, 2011). Other studies found that outgroup-directed emotion plays a more important role in future protesting behaviour .…”
Section: Participation In Collective Action and Self-based Vs Group-supporting
confidence: 78%
See 1 more Smart Citation
“…Several empirical studies that are in line with our findings explain that when performing collective action, the emotion felt by an individual is the group's emotion as a response to the situation experienced by their group, especially anger (Shepherd et al, 2013;Shi et al, 2014; Stewart et al, 2015;van Zomeren et al, 2011). Other studies found that outgroup-directed emotion plays a more important role in future protesting behaviour .…”
Section: Participation In Collective Action and Self-based Vs Group-supporting
confidence: 78%
“…Many studies have proved that group-based anger is a predictor of collective action (Shepherd et al, 2013;Shi et al, 2014;Stewart et al, 2015;van Zomeren et al, 2011). This evidence is relevant for collective action in general, not only for normative action.…”
Section: Emotion As a Predictor Of Collective Actionmentioning
confidence: 99%
“…Previous research examined various aspects of intergroup proximity, such as solidarity or helping, but mainly focused on a relationship in which a more powerful or higherstatus group supported the powerless outgroup (Saab, Tausch, Spears, & Cheung, 2014;Stewart et al, 2016). Previous research examined various aspects of intergroup proximity, such as solidarity or helping, but mainly focused on a relationship in which a more powerful or higherstatus group supported the powerless outgroup (Saab, Tausch, Spears, & Cheung, 2014;Stewart et al, 2016).…”
Section: Who Can Be An Ally? Types Of Groups Mattermentioning
confidence: 99%
“…Specifically, our studies examined to what extent people who belong to third-party groups support a movement depending on whether the movement uses violent or nonviolent strategies, and whether this support is driven by people's perceptions of the movement's members as moral agents sensitive to experiencing pain and suffering when harmed by opposing groups (i.e., by people's attribution of mental capacity to, and perceived morality of, the movement). This support can take many forms: transformation of a neutral third party into a sympathetic one (Oegema & Klandermans, 1994;Simon & Klandermans, 2001), transformation of a sympathetic person into an engaging member of the movement (Oegema & Klandermans, 1994;Van Stekelenburg & Klandermans, 2013), encouragement of regime supporters to stand by or even defect (Nepstad, 2013), encouragement of third parties that support the regime to withdraw their support (Stewart et al, 2015), or encouragement of third parties to help the cause of the movement (Stewart et al, 2015). to succeed.…”
mentioning
confidence: 99%